Pygidiapion De Sousa & Mermudes, a new genus of Apioninae (Brentidae: Apioninae: Apionini) associated with Fabaceae from Brazil, with the description of a new species and transfer of Apion zikani Heller, 1922 - de Sousa, Wesley Oliveira; Mermudes, José Ricardo M. (Zootaxa, 2021)
The genus Pygidiapion De Sousa & Mermudes gen. n., described and illustrated here, includes two species from Brazil: the type-species Pygidiapion zeppelinii De Sousa & Mermudes sp. n. (type-locality: João Pessoa, Paraiba state), which develops in flower buds of Pterocarpus violaceus Vogel (Fabaceae); and Pygidiapion zikani (Heller, 1922) comb. n. (from Apion) (type-locality: Passa Quatro, Minas Gerais state), which develops in flower buds of Dalbergia foliolosa Benth. (Fabaceae). Pygidiapion is defined by the following set of characters: rostrum of males with two elongate longitudinal and punctate latero-ventral sulci; hind wings with small radial window; hypomeral lobes divided by median suture and sternellum distinctly exposed; meso- and metatibiae mucronate; pygidium of the apionine incomplete type; and tegminal plate fused with basal piece. Pygidiapion zeppelinii is diagnosed by: meso- and metatibiae mucronate; pygidium distinctly modified, with deep transverse dorsal sulcus, medially deeper and rounded, and proximal marginal rim angulate (apical flange), corresponding to the distal margin, which is emarginate; tegminal plate fused to basal piece, apical portion of parameroid lobes weakly notched medially, each side of suprafenestral plate with five macrochaetae, fenestral width 1.25 times length, separated by about 3.2 times fenestral width, linea arquata visible, prostegium protruding medially, tegminal apodeme 0.76 as long as basal piece, with apex narrow and rounded. Pygidiapion zikani is distinguished from P. zeppelinii by smaller size; head, rostrum and antennae brownish; scutellum subquadrate; and by association with Dalbergia spp. (Fabaceae). Association principally with the papilionoid group of Fabaceae suggest allocation of the new taxon to the subtribe Oxystomatina.